Selected Problems of Vehicle-Track Interaction in Small-Radius Curves (Current Problems in Rail Vehicles, 2025)
This paper is focused on selected problems of the vehicle-track interaction in small radius curves, which are currently solved at the Faculty of Transport Engineering of the University of Pardubice as part of students' theses. In the first part, attention is paid to the effects of different design concepts of running gear of a six-axle locomotive on the track, with regard to lateral force effects and wear; the Swiss methodology of quantifying the damaging effects of vehicle running on the track is analysed in this context. In the second part, this paper deals especially with the permissible cant of track and steepness of transition curves in the small radius curves. Attention is paid to the limiting factors and their consequences in terms of achievable track speed.
Keywords: vehicle-track interaction; safety against derailment; guiding force; frictional work; wear; transition curve; track speed